Indigenous consultation in Chile: right of participation or self-determination? (Estudios Sociales, 2020)
The purpose of this paper is to develop the contradictions of the international standard of the right to indigenous consultation expressed in the confrontation between two paradigms: a decolonial one of self-determination, and that of a human right to participate within the democratic framework of a State. Discussions of the reliable history - from the mid-19th century - of the discussion of the main instruments of international law referring to indigenous peoples as subjects of international law, and in particular the right to indigenous consultation, are examined. This is complemented by specialized doctrinarian literature and official interpretation agencies. We conclude that there is a paradoxical coexistence to the extent that, even though the participation paradigm has been prioritized in abstract and formally, the weak consolidation of the right to consultation, added to certain particularities, brings with it the increase in the legitimacy of self-determination.
Keywords: indigenous consultation; self determination; human rights; righ to participate; indigenous peoples